Pelaksanaan Program KKN: “Desa Sehat” sebagai Wujud Pengabdian di Wilayah Kelurahan Melebung - Ami Amelia; Nabilla Rahma Putri; Fauziah Hafshoh Maimunah; Amanda aliyah Putri; Annisa Alfatih; Arnila Melina (Jurnal Pengabdian Bidang Kesehatan, 2024)
KKN with the theme KKN “ Saves the Country Through Education” with 2 target missions : Education Mission and Country Mission. These two missions are a vehicle for service so that students can be directly involved in dealing with problems that occur. The implementation of this KKN program has been carried out referring to the situation and needs of the Village. For 1 month at the Melebung Village KKN location, students have carried out various programs planned between the village and the students. The programs that have been implemented are : PHBS, TOGA, Stunting Prevention, simple hydroponics, health care training and various other additional programs. This KKN activity is published in online mass media publications, YouTube channels and also in service journals.